2(x+3)-1=3

Simple and best practice solution for 2(x+3)-1=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)-1=3 equation:


Simplifying
2(x + 3) + -1 = 3

Reorder the terms:
2(3 + x) + -1 = 3
(3 * 2 + x * 2) + -1 = 3
(6 + 2x) + -1 = 3

Reorder the terms:
6 + -1 + 2x = 3

Combine like terms: 6 + -1 = 5
5 + 2x = 3

Solving
5 + 2x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 2x = 3 + -5

Combine like terms: 5 + -5 = 0
0 + 2x = 3 + -5
2x = 3 + -5

Combine like terms: 3 + -5 = -2
2x = -2

Divide each side by '2'.
x = -1

Simplifying
x = -1

See similar equations:

| 7/n=4/8 | | 6(4z-1)-3(z+6)=13(z+1) | | k-1/3=10 | | 4(-6)(-5)-2(-5)(2)= | | 2/5x-12=2 | | 6x+6y+6=0 | | 3*6-12/6 | | x-3/8=1x/3 | | 4x+6=4x-5 | | 6y+18=y+11 | | [[24]/[56]] | | 78=5t-7 | | -7(8x-7)+8(1+5x)=-23 | | 1-2x=3x-11 | | x-3/8=1-x/3 | | 3m+5=25 | | (20a^2b)/(4a^2b2) | | x(x)+3x-10=-6 | | 3x-(5)=4 | | 2a-3=-17 | | 4x+6=5*2x | | 6-x=4(3x-5) | | 5x-88y=120 | | C=(3.14)(12) | | 7c+2=2+5c-5 | | -2(-2u-4)=4n+11 | | 35x+0.10y=25x+0.15y | | x^6-4x^5-45x^4=0 | | -6+-12-6= | | 3(c-12)=15 | | -8(t-4)-(t+6)=5 | | A-4+5a=-16 |

Equations solver categories